Program Sekolahane Arek Suroboyo Kampanye Permainan Tradisional Kepada Siswa SDN Ploso V Surabaya - Arga Pratama Putra (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
Education is an effort to prepare students through guidance, teaching, teaching, and changing the attitude of a child's behaviour in an effort to mature. Through education a human being can control himself and can develop his personality towards a better life. The SAS (Sekolahane Arek Suroboyo) programme campaigns traditional games to students of SDN V Ploso Surabaya. This research aims to overcome overidigitalitation that can damage a child's personality because in modern times now many students can use mobile phones to play online games that cause students to become addicted and forget the lessons at school. The problem here is that teachers are required to The problems raised are based on the lack of learning media, so teachers are required to be creative in choosing the right learning media for students so that they are not bored in class. The method used in this research is Qualitative Method to see how children who do traditional games with those who do modern games and the effect on child development both motor and cognitive. The result is that children who do traditional games are much more developed in their abilities and character. The population in this study is all third grade students of SDN Ploso V Surabaya to see how children who play traditional games in the modern era and the effects on children's development both motor and cognitive.